Managing Metadata for Philatelic Materials - Ozeran, Megan (Information Technology and Libraries, 2017)
Stamp collectors frequently donate their stamps to cultural heritage institutions. As digitization becomes more prevalent for other kinds of materials, it is worth exploring how cultural heritage institutions are digitizing their philatelic materials. This paper begins with a review of the literature about the purpose of metadata, current metadata standards, and metadata that are relevant to philatelists. The paper then examines the digital philatelic collections of four large cultural heritage institutions, discussing the metadata standards and elements employed by these institutions. The paper concludes with a recommendation to create international standards that describe metadata management explicitly for philatelic materials.